Clinical Presentations of Coenzyme Q(10) Deficiency Syndrome - Quinzii, Catarina M. (S. Karger AG, 2014)
Coenzyme Q(10) (CoQ(10)) deficiency is a clinically and genetically heterogeneous syndrome which has been associated with 5 major clinical phenotypes: (1) encephalomyopathy, (2) severe infantile multisystemic disease, (3) nephropathy, (4) cerebellar ataxia, and (5) isolated myopathy. Of these phenotypes, cerebellar ataxia and syndromic or isolated nephrotic syndrome are the most common. CoQ(10) deficiency predominantly presents in childhood. To date, causative mutations have been identified in a small proportion of patients, making it difficult to identify a phenotype-genotype correlation. Identification of CoQ(10) deficiency is important because the disease, in particular muscle symptoms and nephropathy, frequently responds to CoQ(10) supplementation.